A GBT Model for the Analysis of Composite Steel–Concrete Beams with Partial Shear Interaction. (November 2015) - Taig, Gerard; Ranzi, Gianluca; Dias-da-Costa, Daniel; Piccardo, Giuseppe; Luongo, Angelo
Abstract: Composite steel–concrete beams represent an efficient form of construction for building and bridge applications. In this structural arrangement, the composite action is provided by means of a shear connection placed at the interface between the steel beam and the concrete slab, and this is commonly specified in the form of shear connectors. In this system, the structural rigidity is dependent on the deformability of the shear connection and this kinematic condition is usually referred to as partial shear interaction. In this context, this paper presents a theoretical model to study the partial shear interaction behaviour of composite steel–concrete beams in the framework of GBT. The effects of longitudinal slip between the concrete slab and steel beam are accounted for by taking into account the deformability of shear connectors during the evaluation of the warping components of the deformation modes. The proposed approach falls within a category of cross-sectional analyses available in the literature for which a suitable set of deformation modes, including conventional, extension and shear modes, is chosen from dynamic analyses. This method is applicable to open, closed and partially-closed cross-sections with one or more shear connections. A numerical example of a composite bridge is presented, with the results validated against those obtained from a shell finite element model developed in ABAQUS/Standard. The effect of different finite elements used in the GBT cross-sectional analysis is considered, in particularly highlighting how they influence the stress distributions induced in the composite section.